Spatial relationships of road network and cellular coverage based on the Open Geodata: review and user case of Irkutsk Region - E. S. Podolskaia (Российский технологический журнал)
Geographic information technologies and data are widely used to identify a variety of spatial relationships. The paper is devoted to the study of the mutual location between the road network (as exemplified by the public roads network) and cellular coverage of the Russian telecom operators on the territory of Russia. Transport researches are characterized with an emphasis of GIS projects. Then, an overview of modern web services, Open Data and Open Source developments in transport projects is made. The data, geodata services and web projects of cellular coverage for the territory of Russia are described by the examples of Russian-language sources. The practical part of the study shows the global transport accessibility raster datasets for the test region of Russia (Irkutsk Region, Siberian Federal District). An analysis of spatial relationships between roads and cellular coverages provided by VimpelCom/ Beeline, Megafon and MTS is based on the Open Data in the Open Source GIS application QGIS. Coverage varies between 63% (VimpelCom for the buffer zone of 2.5 km) and 94% (Megafon for the zone of 10 km), where 100% is the total number of cells (polygons) within the network of a respective operator in the region. We have noted that Open Data on the public road network and cellular communication for the territory of Russia differ by region, the studied communication datasets and data services do not contain significant attributive information, they consist of polygon geometry only. Frequency of their updates depends on the operating companies. The operators then provide the data for the publication to the Russian ministries and regional administrations.